Imperial court finance chamber on the Johannesgasse - Geissler, Maria (publisher)::::::::::::::: (Austria; Vienna; Maria Geissler, 2020)
Miniature color engraving of the Hofkammer, the imperial court finance chamber, on the Johannesgasse in Vienna